Adolescent experiences of mistreatment during childbirth in health facilities: secondary analysis of a community-based survey in four countries. (21st March 2022) - Irinyenikan, Theresa Azonima; Aderoba, Adeniyi Kolade; Fawole, Olufunmilayo; Adeyanju, Olusoji; Mehrtash, Hedieh; Adu-Bonsaffoh, Kwame; Maung, Thae Maung; Balde, Mamadou Dioulde; Vogel, Joshua P; Plesons, Marina; Chandra-Mouli, Venkatraman; Tunçalp, Özge; et al.
Abstract : Introduction: Pregnancy and childbearing among adolescents—especially younger adolescents—is associated with health complications and lost opportunities for education and personal development. In addition to established challenges adolescents and young women face in sexual and reproductive healthcare, evidence suggests that they also face mistreatment during childbirth. Methods: This is a secondary analysis of the WHO study 'How women are treated during facility-based childbirth' cross-sectional community survey in Ghana, Guinea, Myanmar and Nigeria. We used descriptive analysis to assess experiences of mistreatment among adolescents (15–19 years) and young women (20–24 years) and multivariable logistic regression models to assess the association between experiences of mistreatment and satisfaction with care during childbirth. Results: 862 participants are included (15–19 years: 287, 33.3%; 20–24 years: 575, 66.7%). The most common mistreatment was verbal abuse (15–19 years: 104/287, 36.2%; 20–24 years: 181/575, 31.5%). There were high levels of poor communication (15–19 years: 92/287, 32.1%; 20–24 years: 171/575, 29.7%), lack of supportive care (15–19 years: 22/287, 42.5%; 20–24 years: 195/575, 33.9%) and lack of privacy (15–19 years: 180/287, 62.7%; 20–24 years: 395/575, 68.7%). Women who were verbally abused were less likely to report satisfaction with care (adjusted OR (AOR): 0.19, 95% CI: 0.12 to 0.31) and less likely to recommend the facility (AOR: 0.24, 95% CI: 0.15 to 0.38). There were similar reports among those who were physically abused, had long waiting time, did not mobilise and did not give consent for vaginal examinations. Conclusion: Our study shows that adolescents and young women mistreatment during childbirth, contributing to low satisfaction with care. It is critical to recognise adolescents and young women's unique needs in maternal healthcare and how their needs may intersect with social stigma around sex and pregnancy.